The Swedish macroeconomic policy framework - Lars Calmfors (Research Institute of Industrial Economics (IFN), 2015)
The paper describes the monetary and fiscal policy frameworks in Sweden and analyses how they were established as well as current challenges. Sweden provides a good example of how deep economic crisis, in interaction with independent thinking by academics and other experts as well as policy influences from abroad, can lead to fundamental reforms of policy frameworks. It remains to be seen whether it will be possible in Sweden to adapt the monetary and fiscal frameworks to changed circumstances, while still preserving the benefits they have delivered.
Keywords: E58; H61; 330; Independent central banking; inflation targeting; fiscal rules; fiscal councils